ABOUT THE LANGUAGES OF THE HUMAN BRAIN - Karimov N., Tirkashev L.Ya. , Xolmatov T.Q. , Abduraxmonov ?. (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The article describes the ongoing processes of the human brain about the formation of structures and channeling switches. Transformation of information in the human brain system, as well as encoding and decoding of information. This article discusses the language of the human brain and language codes